Pharmacokinetics, clot strength and safety of a new fibrinogen concentrate: randomized comparison with active control in congenital fibrinogen deficiency. (22nd January 2018) - Ross, C.; Rangarajan, S.; Karimi, M.; Toogeh, G.; Apte, S.; Lissitchkov, T.; Acharya, S.; Manco‐Johnson, M. J.; Srivastava, A.; Brand, B.; Schwartz, B. A.; Knaub, S.; et al.
Abstract : Essentials Congenital afibrinogenemia causes a potentially life‐threatening bleeding and clotting tendency. Two human fibrinogen concentrates (HFCs) were compared in a randomized pharmacokinetic study. Bioequivalence was not shown for AUCnorm, which was significantly larger for the new HFC. Increases in clot strength were comparable, and no thromboses or deaths occurred in the study. Summary: Background: Human fibrinogen concentrate (HFC) corrects fibrinogen deficiency in congenital a‐/hypofibrinogenemia. Objectives: To assess pharmacokinetics (PK), effects on thromboelastometry maximum clot firmness (MCF), and safety of a new double virus‐inactivated/eliminated, highly purified HFC vs. active control. Patients/Methods: In this multinational, randomized, phase II, open‐label, crossover study in 22 congenital afibrinogenemia patients aged ≥ 12 years, 70 mg kg −1 of new HFC (FIBRYGA, Octapharma AG) or control (Haemocomplettan ® P/RiaSTAP™, CSL Behring GmbH) were administered, followed by crossover to the other concentrate. Fibrinogen activity, PK and MCF in plasma were assessed. Results: The concentrates were not bioequivalent for the primary endpoint, AUCnorm (mean ratio, 1.196; 90% confidence interval [CI], 1.117, 1.281). Remaining PK parameters ( C maxnorm, IVR, t 1/2, MRT) reflected bioequivalence between concentrates, except for clearance (mean ratio, 0.836; 90% CI, 0.781, 0.895) and V ss (mean ratio, 0.886; 90% CI, 0.791, 0.994). Mean AUCnorm was significantly larger for the new HFC (1.62 ± 0.45 vs. 1.38 ± 0.47 h kg g L −1 mg −1, P = 0.0001) and mean clearance was significantly slower (0.665 ± 0.197 vs. 0.804 ± 0.255 mL h −1 kg −1, P = 0.0002). Mean MCF increased from 0 mm to 9.68 mm (new HFC) and 10.00 mm (control) 1‐hour post‐infusion (mean difference, −0.32 mm; 95% CI, −1.70, 1.07, n.s.). No deaths, thromboses, viral seroconversions or serious related adverse events occurred. Conclusions: Bioequivalence was not demonstrated for AUCnorm, clearance and V ss . Larger AUCnorm and slower clearance were observed for the new HFC. Remaining pharmacokinetic parameters reflected bioequivalence to control. Safety profiles and increases in clot strength were comparable between concentrates.